HUBUNGAN PENGETAHUAN DENGAN SIKAP REMAJA PUTERI TENTANG DETEKSI DINI KANKER PAYUDARA MELALUI SADARI (PERIKSA PAYUDARA SENDIRI) DI WILAYAH KERJA PUSKESMAS UJUNG KUBU KABUPATEN BATUBARA TAHUN 2022 - Irmawati, Irmawati; Nopalina Suyanti Damanik (Pusat riset dan Inovasi Nasional, 2022)
One effort that can be done to control breast cancer is to carry out primary prevention such as controlling risk factors and increasing communication, information and education. Secondary prevention is carried out through early detection of breast cancer, namely breast self-examination (BSE). This study aims to determine the level of knowledge and attitudes of young women about early detection of breast cancer through self-examination (breast self-examination) in the working area of ​​the Ujung Kubu Health Center, Batubara Regency in 2022. This study used a collaborative research design with a cross-sectional approach. With a total population of all young women in the Working Area of ​​the Ujung Kubu Health Center, Batubara Regency, namely 130 pure women with a sample of 58 using the simple random sampling method. Data collection in March-June 2022. This analysis was carried out to test the hypothesis using the Chi Square test at significant and if the p-value < 0.05. Based on the results of the study between knowledge and BSE actions, the Chi Square statistical test obtained a p value = 0.010 so that p <0.05. And the attitude with the BSE action that the Chi Square statistical test obtained a p value = 0.038 so that p <0.05 then H0 is rejected and Ha is accepted. There is a Relationship between Knowledge and Attitudes of Young Women About Early Detection of Breast Cancer Through Self-Examination (Breast Self-Examination) in the Working Area of ​​the Ujung Kubu Health Center, Batubara Regency in 2022. It is hoped that this can be one of the therapies given to young women to prevent breast cancer from being carried out as early as possible.